Organization Design for International Construction Business - Peh Lu, Chang. (Springer Berlin Heidelberg : Imprint: Springer, 2013)
The book explains how Gravitational Distance and the System of Cities influence transnational construction-related firms when they venture overseas. The study presented in the book internalizes the characteristics of home and foreign cities, and of transnational firms, to develop situational business strategies and organization designs in terms of Strategy, Structure, Systems, Leadership Style, Firms Skills, Staffs characteristics, Shared Values and Supply Chain. The book presents the findings of surveys and interviews with managers and professionals in eight different Asian cities stretching from Singapore to China. The findings are then used to develop business solutions in the form of a Decision Support System (DSS) for transnational construction firms, helping them to adopt an appropriate organization design strategy when they venture into overseas markets. Issues relating to globalization, competitiveness, risk management, communications, networks, government interference, business strategies, organization structures and systems in the context of international construction business are discussed together with corresponding recommendations for implementation. Although construction-related firms were used as the basis for the field studies, the lessons learned are equally applicable for organizations in other industries.